Evaluasi Kesehatan Sapi Perah - Reni Ita Safitri; Dian Wahyu Harjanti; Enny Tantini Setiatin (Jurnal Agripet, 2015)
(Health evaluation of dairy cows)ABSTRACT. This study was conducted to evaluate the health status of dairy cows in dairy barn of Animal and Agricultural Sciences Faculty, Diponegoro University. Physiological status such as rectal temperature, arterial pulse and respiratory rate were evaluated. Samples collected were feces, urine and roughage. The feces samples were analyzed using Witchlock method, the grass samples were analyzed using sedimentation method and the urine samples were observed under microscope after centrifugation at 1500 rpm. The result was analyzed using descriptive analysis. The result showed from the examination of physiology (heifer, pregnant cow and lactating cow) that the average of pulses rate was ranged respectively between 53-60 times/minutes, 53,6-55,5 times/minutes dan 55,1-58,8 times/minutes. Breath frequency was ranged between 17,1-18,1 times/minutes, 18-18,3 times/minutes and 16-17 times/minutes and rectal temperature was ranged between 38,3-38,5oC, 38,5-38,6oC dan 38,4-38,5oC. Although, there was found endoparasites of nematoda in feces, crystal (calcium oxalate monohydrate and dihydrate, struvite) in urine, and ectoparasites of ixodidae in grass but then all dairy cows evaluated during research indicated physiologically health. In conclusion : all dairy cows were physiologically health. Future examination, sanitation and treatments should be conducted to maintain the animals health.